On the strenght of punjabi asphalt - Jurášek, Michal; Cabalka, Josef; Drašar, Pavel (Chemické listy, 2023)
Mumio (shilajit), a substance similar to asphalt or resin that oozes from rocks during hot sunny days, mostly in caves in the Himalayas, is known as a medicinal substance in Eastern medicine. It is slowly being accepted by Western healing as well as medicine. It mainly contains fulvic acids, humic acids and a number of other substances. The article mainly summarizes recent information about this substance.
Keywords: mumio; Complementary Therapies; lidé; tradiční lékařství; komplementární terapie; léčivé přípravky; Humans; Pharmaceutical Preparations; Medicine, Traditional